Electrodermal Activity Study of Aesthetic Emotions Through Pleasant and Unpleasant Stimuli - Ajeng Rintan Septiani; Sri Kusrohmaniah; Supra Wimbarti; Noor Akhmad Setiawan (Psympathic : Jurnal Ilmiah Psikologi, 2026)
Aesthetics are inseparable from the involvement of emotions; aesthetic emotion appears as an emotion that arises when exposure to an aesthetic stimulus. Aesthetic emotion remains limited to self-report scale measurements and doesn’t provide physiological evidence. One of the measurements of aesthetic emotions can be conducted by observing emotional arousal through electrodermal activity (EDA). This study aimed to observe the arousal of aesthetic emotions through electrodermal activity that is restricted to the musical domain using auditory stimuli. The aesthetic audio stimuli are pleasant and unpleasant music as a representation of positive and negative emotions. The hypothesis assumed that there are arousal differences in aesthetic emotions from exposure to pleasant and unpleasant stimuli. The study experimented a within-group design, involving 20 non-musician students aged 20-28 years. Participants were given an aesthetic music stimulus from the Film Music Stimulus Set (FMSS), which was included in the category of pleasant and unpleasant music. EDA measurements calculate the mean amplitude of the phasic component as an indicator of emotional arousal during stimulus exposure. Experiments also provide the Aesthetic Responsiveness Assessment (AreA) to see individual responsiveness toward aesthetic stimuli. The results provide evidence related to the hypothesis that arousal of aesthetic emotions during exposure to pleasant and unpleasant stimuli has significant differences. The relationship between aesthetic responsiveness and EDA is noticeable by recognizing the type of presented stimuli. The findings in this study provide an idea related to the application of aesthetic stimuli in various contexts, that music that provides pleasant effects tends to provide more intense emotional arousal.